Nutrition for Health and Fitness: Fiber in Your Diet - Linda B. Bobroff (EDIS)
Whether you call it dietary fiber, fiber, or roughage, eating a diet rich in this food component is good for your health. This 8-page fact sheet provides tips on how to include foods with fiber in your diet. Written by Linda B. Bobroff, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised March 2018. http://edis.ifas.ufl.edu/he697